Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/jn/nxz231
|View full text |Cite
|
Sign up to set email alerts
|

A Moderate-Fat Diet with One Avocado per Day Increases Plasma Antioxidants and Decreases the Oxidation of Small, Dense LDL in Adults with Overweight and Obesity: A Randomized Controlled Trial

Abstract: Background Avocados are a nutrient-dense source of MUFAs and are rich in antioxidants. Avocados have an additional LDL cholesterol (LDL-C) lowering effect beyond that observed when their MUFAs are substituted for SFAs, especially on small, dense LDL (sdLDL) particles, which are susceptible to in vivo oxidation and associated with increased risk of cardiovascular disease (CVD). Objectives We investigated whether a healthy diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 47 publications
2
51
0
1
Order By: Relevance
“…As evidence linking cardiometabolic health with brain health and function continues to grow (53,54), we also hypothesize that the relationship between avocado intake and better cardiometabolic health may provide explanation for our findings (29)(30)(31)(32)(33)(34). For instance, avocados have micronutrients that may benefit blood pressure and avocado interventions have been shown to lower LDL and raise HDL in patients with hypercholesterolemia (30)(31)(32)34) and improve peripheral blood flow acutely after consumption (29,33).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…As evidence linking cardiometabolic health with brain health and function continues to grow (53,54), we also hypothesize that the relationship between avocado intake and better cardiometabolic health may provide explanation for our findings (29)(30)(31)(32)(33)(34). For instance, avocados have micronutrients that may benefit blood pressure and avocado interventions have been shown to lower LDL and raise HDL in patients with hypercholesterolemia (30)(31)(32)34) and improve peripheral blood flow acutely after consumption (29,33).…”
Section: Discussionmentioning
confidence: 60%
“…While the AFT and DSST scores were significantly better for avocado consumers in our unadjusted model, the significance was attenuated in the adjusted models. Given avocado consumption is growing dramatically worldwide, and research has shown the cardiometabolic benefits of eating avocados through the effects of various dietary components, phytochemical, and nutrients that avocados include as discussed by Silva Caldas et al (29)(30)(31)(32)(33)(34), it's relevant to study the cognitive benefits of avocado intake within a large population cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A ausência de toxicidade das infusões avaliada pelo teste de germinação em Allium cepa é corroborada pelos dados da literatura, sendo observado que as infusões de cavalinha (Baracho et al, 2009), do hibisco (Gad et al, 2020) e das folhas de abacate (Nicolella et al, 2017) não apresentam toxicidade. Além disso, a ausência de toxicidade pode estar relacionada com os potenciais antioxidantes da cavalinha (Masłowski et al, 2020), do hibisco (Chiaino et al, 2020) e do abacate (Wang et al, 2020), que podem ser atribuídas aos flavonoides e ácidos fenólicos que os frutos apresentam (Masłowski et al, 2020).…”
Section: Resultsunclassified
“…Half of them had a significant drop in cholesterol, whereas none of the others had an increase. Avocados may not be a bad option for folks with excessive cholesterol or triglyceride levels [37,55].…”
Section: A Cure For High Cholesterolmentioning
confidence: 99%
“…The fruit contains alpha-carotenes, which have antioxidant characteristics and may protect against the oxidation of the 'bad' LDL-cholesterol, lowering the risk of atherosclerosis [55]. Avocado consumption may also help those with atherosclerosis-related angina pectoris.…”
Section: Atherosclerosis Angina Pectoris and Alzheimer's Diseasementioning
confidence: 99%